Admissibility of Electronic Evidence in Islamic Law and US Law- Need for a New Corroboration Theory - Hafsa Abbasi; Dr. Asim Iqbal (MEI, 2023)
As the nature of civilization change with the passage of time, both in social and technological terms, the rules of legislatures must also change accordingly.” Electronic evidence has embedded deep into the roots of society. It requires a new corroboration theory for Islamic law accordingly. As electronic evidence possesses a different nature than physical evidence. Sometimes it is regarded as documentary evidence, sometimes as circumstantial evidence and sometimes as something purely dependent on technical opinion. Previously oral testimony had prime importance which was replaced with documentary evidence and now electronic records. These changes must be incorporated by Islamic law theories as well. In fact, there is a need to over howl previous principles of Islamic law and replace the new one’s which are appropriate and not repugnant to philosophy of Sharī‘ah. The present research shall try to slightly contribute to this important point.